2020
DOI: 10.3390/su12156192
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Lens upon Industrial Symbiosis Dynamics: The case of Persian Gulf Mining and Metal Industries Special Economic Zone

Abstract: Industrial Symbiosis (IS) is a collaboration between nearby industrial plants to exchange waste material and energy and achieve economic and environmental benefits that cannot be obtained individually. IS emergence in a cluster requires both technical potentials for material and energy exchange and social readiness for collaboration. In this paper, to gain insight into IS dynamics in emerging industrial clusters; we investigate shared concepts governing actors’ behavior in the form of rules and regulations, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
0
14
0
2
Order By: Relevance
“…Noori et al [19] support the notion that actors' roles in the collaboration clearly affect what drives them to participate. They show that driving factors differ between the individual companies and the facilitators (in [19] referred to as the cluster management).…”
Section: Actors' Roles In Collaborationmentioning
confidence: 94%
See 2 more Smart Citations
“…Noori et al [19] support the notion that actors' roles in the collaboration clearly affect what drives them to participate. They show that driving factors differ between the individual companies and the facilitators (in [19] referred to as the cluster management).…”
Section: Actors' Roles In Collaborationmentioning
confidence: 94%
“…Noori et al [19] support the notion that actors' roles in the collaboration clearly affect what drives them to participate. They show that driving factors differ between the individual companies and the facilitators (in [19] referred to as the cluster management). For the individual companies, economic benefits are among the most important factors, while eco-efficiency is an important driver for the cluster management.…”
Section: Actors' Roles In Collaborationmentioning
confidence: 94%
See 1 more Smart Citation
“…Household and industrial electricity prices were obtained from Iran's power generation and distribution company databases (Noori, 2020b). A previous institutional study showed no explicit penalties or limitations for waste disposal applied in PGSEZ (Noori et al, 2020). Therefore waste disposal cost was set equal to zero in the model.…”
Section: Input Datamentioning
confidence: 99%
“…The Linny-R models of the four configurations and assumptions on other economic parameters used in the models are summarized in the Supporting Information. are significantly lower than EU average prices and have not increased dramatically during the last years (Noori et al, 2020). Energy prices were changed under three scenarios to study the impact of institutional conditions on IS emergence.…”
Section: Configurationsmentioning
confidence: 99%